Growth and sexual development of javanese thin-tailed ewe lambs as affected by moderate internal parasite burden - I. K. Sutama (Hemera Zoa, 1991)
The effect of a moderate burden of internal parasites on growth and sexual development of Javanese thin-tailed (JIT) ewe lambs was studied from weaning at 13 weeks of age to puberty (first oestrus group (T) was infected with third stage mixed larvae comprised of 840 Haemonchus spp., 150 Cooperia spp., 255 Oesophagostomum spp., 240 Tri chostrongylus spp., and 15 Strongyloides spp. The lambs were fed elephant grass and concentrate (Beef0kwik, Cargill) ad lib. throught the experiment period. The result showed that a moderate parasite burden did not significantly influence growth and sexual development of JTT ewe lambs reared under research station conditions. However, group T ewe lambs consumed 8% more feed than group C. The possibility that JTT sheep may have a high resistance to internal parasite warrants further investigation.